Kajian Identifikasi dan Implementasi Kebijakan Perlindungan LP2B di Kabupaten Pekalongan - Nugara, Nugara; Rudiarto, Iwan (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2017)
The government's efforts in realizing food security and food sovereignty are being faced with the problem of the high conversion of agricultural land. To that end, the government made Law Number 41 of 2009 on the Protection of Sustainable Food Agricultural Land (LP2B) decentralized to the regions. Pekalongan regency potential as a producer of food crops, but have not had clear rules to protect potential of land conversion. Pekalongan has set LP2B area, but there is no locus. This study visits of conversion of agricultural land happens, the identification of suitable agricultural land to LP2B criteria, as well as the potential and constraints in implementation LP2B Protection Policy. The method used is the method of spatial and qualitative methods (parallel mixed method). As a result, agricultural land continues to decline due to the conversion. Of the total area of 30734.39 hectares of agricultural land, only 18959.35 hectares in accordance with the criteria LP2B. This figure does not meet predetermined allocation (24 195 hectares). In LP2B protection policy implementation, there is some potential and constraints. Typical constraints include unclear regulations, no socialization, lack of commitment to the community, lack of quantity and quality of human resources, as well as the lack of supporting facilities. Meanwhile, the potential that is where team IPPT can minimize the occurrence of agricultural land conversion. Pekalongan regency potential as one of the producers of food crops (rice) should be protected from the threat of the trend of agricultural land conversion. Pekalongan regency government needs to maximize potential and minimize constraints, and implement existing solutions that LP2B protection policy implementation goes well. Thus, the area of agricultural land that is to remain sustainable and can support food security both at the regency, provincial, and national levels.